Contemporary experience of education digitalization - V. V. Godin; A. E. Terekhova (Вестник университета, 2021)
The article considers the evolution, forms and current situation in the field of education based on information technologies (ITE). The authors investigate directions of changes in the educational sphere as a form of activity, as well as the system and process of knowledge transfer under information and communication technologies (ICT) influence. The paper defines the general properties of the forms of education, based on information technologies. The authors use as a tool of studying the impact of the information and communication technologies on educational institutions and on a learning process the idea of a value chain and employees routine loops reflection in it. The study highlights three areas in which information and communication technologies are changing educational organizations: pedagogics, infrastructure, and organization. The article shows how these changes are seen in the value chain. The paper considers a number of trends in the widely understood process of digitalization of education, the COVID-19 pandemic impact on the development of on-line education, evaluates the existing experience of such education and the limits of its applicability.